The multi-trip vehicle routing problem with increasing profits for the blood transportation: An iterated local search metaheuristic. (August 2022) - Pirabán-Ramírez, Andrea; Guerrero-Rueda, William Javier; Labadie, Nacima
Abstract: This paper studies a multi-trip routing problem of a shuttle fleet to transport blood units from collection sites to a blood center. In this problem, the blood units intended to produce platelets and cryoprecipitate must be processed within eight hours from their donation and arrive at the blood center at a time less than its closing time to guarantee enough processing time. Since it is assumed that blood units are donated at a collection site following a constant ratio over its operating hours, this problem is modeled as a multi-trip vehicle routing problem with increasing profits for which a mixed-integer linear programming formulation is proposed. A hybrid iterated local search metaheuristic and an extended version are developed as solution methods. The extended version includes a mixed-integer linear programming component into the local search of the hybrid metaheuristic to optimize the decision on the departure times of the trips. The solution methods are tested on a new set of instances based on the blood collection system of Bogota, Colombia. Highlights: Whole blood to get blood components and time limits to process platelets are studied. The problem formalization and its mathematical programming model are included. A metaheuristic and a matheuristic are proposed as solution methods. A new set of instances based on a real-world case is presented. Tests validate the applicability of the methods and provide the best-known solutions.